External Treatment of Pyritum for Musculoskeletal Trauma: a protocol for systematic review - Ji Hye Hwang; Su Hyun Choi (Journal of Pharmacopuncture, 2023)
Objectives: Musculoskeletal trauma is a common type of injury that can result from damage to the muscular or skeletal system and has been recognized as a leading cause of death and disability worldwide. This study aims to analyze the efficacy of Pyritum external treatment for musculoskeletal trauma.Methods: Randomized controlled trials evaluating the external treatment effect of Pyritum on various types of musculoskeletal traumatic injuries will be considered and identified in the searches of eight databases from their inception to Feb 2023. There will be no restrictions with respect to the publication status, language, or country. The experimental intervention group will be treated with external application of Pyritum alone or in combination with other therapies, and the comparator intervention group will include all types of control interventions. The primary outcome will be measured as treatment efficacy rate, and secondary outcomes will include pain reduction, pain disappearance time, swelling, joint function, and recovery period. Assessment of the methodological quality of this study will be concluded using the risk of bias assessment recommended by the Cochrane Collaboration. If there are sufficient numbers of studies per group in terms of specific rating scales to compare the treatment effects of Pyrium alone and combined external treatment groups, we will consider subgroup analysis.Results: This systematic review will be conducted in compliance with the PRISMA-P statement.Conclusion: We will conduct an extensive search on the proposed topic within the available literature and provide systematic evidence for the efficacy and safety of external application of Pyritum for all types of musculoskeletal trauma. The evidence generated will help design interventions for the external use of Pyritum for this patient group.